Vaccine design by immunoinformatics against HCV: Chemical characterization and prediction of T-cell epitopes (Research, Society and Development, 2021)
Hepatitis C is a disease that affects the liver causing its inflammation, reaching thousands of people every year, however currently there are no vaccines for the virus responsible for the disease, HCV, although studies are already carried out on its feasibility. Therefore, reverse vaccinology can be of great help in detecting promising targets for use as a vaccine antigen and concomitantly formulating an effective vaccine. The respective work aims to obtain relevant data for the design of promising vaccines against HCV through the use of bioinformatics tools. Therefore, after the virus sequences were obtained from the National Center for Biotechnological Information (NCBI), analyzes of the antigenic potential were carried out using VaxiJen v.2.0. and from ANTIGENpro, together with AlgPred, the allergenic potential was verified, soon after the proteins were verified and selected, they would proceed to the next steps where they were submitted for the characterization of the physicochemical properties, through and the prediction of T cell epitopes was performed on NetTepi. Among the results obtained, it can be noted that the E2 protein was the only one to demonstrate allergenicity, whereas the E1 protein did not present antigenic potential and the other proteins were classified as unstable, following only the NS4a protein for prediction of T cell epitopes.